Efficacy of Laparoscopic Hepatectomy versus Open Surgery for Hepatocellular Carcinoma With Cirrhosis: A Meta-analysis of Case-Matched Studies - Pan, Yu; Xia, Shunjie; Cai, Jiaqin; Chen, Ke; Cai, Xiujun (Frontiers in Oncology, 2021)
Background The role of laparoscopic hepatectomy (LH) in hepatocellular carcinoma (HCC) with cirrhosis remains controversial and needs to be further assessed. The present meta-analysis aimed to compare the surgical and oncological outcomes of LH with those of open hepatectomy (OH) for HCC with cirrhosis. Methods The PubMed, Embase, and Cochrane Library databases were searched for studies comparing LH and OH until Mar 2021. Weighted mean differences (WMDs), odds ratios (ORs), and hazard ratios (HRs) were calculated for continuous, dichotomous, and long-term variables, respectively, with 95% confidence intervals (CIs). Subgroup analysis was performed according to different resection types: major resection and minor resection. The meta-analysis was performed using the STATA 12.0. Results A total of 16 case-matched studies (784 patients in the LH group and 1,191 patients in the OH group.) were included in this meta-analysis. In terms of primary outcomes, LH was associated with decreased overall complication rate (OR 0.57; 95% CI 0.46 to 0.71; P <0.01), major complication rate (OR 0.52; 95% CI 0.33 to 0.82; P < 0.01), postoperative mortality (OR 0.27; 95% CI 0.11 to 0.66; P <0.01), 1-y overall survival (OS) rate (HR 0.48; 95% CI 0.31 to 0.73; P <0.01), 2-y OS (HR 0.61; 95% CI 0.45 to 0.83; P < 0.01), and 5-y OS (0.67; 95% CI 0.53 to 0.85; P < 0.01). With respect to secondary outcomes, blood loss (WMD −69.16; 95% CI −101.72 to −36.61; P < 0.01), length of hospitalization (LOH) (WMD −2.65; 95% CI −3.41 to −1.89; P < 0.01), minor complication rate (OR 0.70; 95% CI 0.53 to 0.94; P = 0.02), postoperative liver failure (OR 0.60; 95% CI 0.38 to 0.95; P = 0.03), and postoperative ascites (OR 0.44; 95% CI 0.28 to 0.72; P < 0.01) was lower in LH than in OH. No significant differences in operation time (P = 0.07), transfusion rate (P = 0.05), 1-, 2-, and 5-year DFS rate (1-year, P = 0.08; 2-year, P = 0.08; 5-year, P = 0.23) were noted between LH and OH. Subgroup analysis based on minor resection revealed that LH had similar favored outcomes in comparison with those in the overall pooled analysis. However, LH had a longer operation time than OH in the setting of major resection (P < 0.01). Conclusion LH is technically feasible and safe for selected HCC patients with cirrhosis. LH can achieve favored short-term and long-term oncological outcomes in minor liver resection. Laparoscopic major hepatectomy (LMH) seems to offer some advantages over the open approach; however concerns about surgical and oncological safety remain. More evidence on LMH is warranted before expanding its indication to patients with cirrhosis.